HUBUNGAN EFIKASI DIRI DAN PERSEPSI DUKUNGAN ORGANISASI DENGAN KETERIKATAN KERJA PADA KARYAWAN - Goman, Evita; Matulessy, Andik; Rini, Amanda Pasca (Faculty of Science and Technology University of Pramita Indonesia, 2024)
Work is a form of conscious attachment between individuals and objects. This attachment is actively carried out to achieve work goals. Every person who works for a company receives compensation in accordance with the agreement In reality, not all human resources are able to behave productively to carry out their duties and obligations. There are many cases that deviations are made during the work process. This deviation disrupts the existing work system. The reason of this consider is to look at work connection with self-efficacy factors and organizational recognitions. The consider utilized quantitative strategies with different relapse investigation. The results of the study of 203 participants stated that perceptions of organizational support contributed more to employee engagement.